A correlation between juvenile hormone deficiency and vitellogenic oocyte degeneration in Drosophila melanogaster. - Wilson, T.G. (Wilhelm Roux's archives of developmental biology, 1982)
It is known from previous work that juvenile hormone (JH) is required to initiate vitellogenin uptake into maturing oocytes ofDrosophila melanogaster, but additional requirements for this hormone during oocyte maturation have not been fully understood. To determine if early vitellogenic oocytes (stages 8 and 9) require JH for continued development, these oocytes were transplanted toDrosophila female and male hosts which were rendered deficient in JH by three methods. Implanted stage 9 and usually stage 8 oocytes were found to degenerate in JH-deficient hosts unless ZR-515, a JH analogue, was applied to the host shortly after implantation.These results were confirmed during in situ ovary development. JH deficiency was produced in gravid females, and ovaries examined at subsequent time intervals were found to be deficient in stage 8-10 oocytes as early as 6 h after treatment. Degenerating oocytes corresponding to these stages were commonly found. ZR-515 prevented oocyte degeneration during at least the first 8 h and continued to support stage 8-10 oocyte development 24 h after application to these females. The results suggest that JH is required not only for initiation but also for continuation of vitellogenin uptake and oocyte development.